2013
DOI: 10.1016/j.csr.2013.10.003
|View full text |Cite
|
Sign up to set email alerts
|

A 100-year long record of alkenone-derived SST changes by Southeast Greenland

Abstract: Publisher's copyright statement: NOTICE: this is the author's version of a work that was accepted for publication in Continental Shelf Research. Changes resulting from the publishing process, such as peer review, editing, corrections, structural formatting, and other quality control mechanisms may not be reected in this document. Changes may have been made to this work since it was submitted for publication. A denitive version was subsequently published in Continental Shelf Research, 71, 1 December 2013, https… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
11
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 10 publications
(14 citation statements)
references
References 58 publications
3
11
0
Order By: Relevance
“…Alkenone biomarkers, mainly produced by the coccolitophorid Emiliana huxleyi , have successfully been used for SST reconstructions in this region 17 , 18 . This method was previously applied to core ER07 for reconstructing the SST variability of the last 100 years 17 . Our new 1700-year long record shows SSTs ranging from 6 to 12.6 °C (Fig.…”
Section: Settingmentioning
confidence: 99%
“…Alkenone biomarkers, mainly produced by the coccolitophorid Emiliana huxleyi , have successfully been used for SST reconstructions in this region 17 , 18 . This method was previously applied to core ER07 for reconstructing the SST variability of the last 100 years 17 . Our new 1700-year long record shows SSTs ranging from 6 to 12.6 °C (Fig.…”
Section: Settingmentioning
confidence: 99%
“…Many tidewater glaciers in southeast and west Greenland show significant changes in velocity and consequent ice flux to the ocean since 2000 (e.g. Andresen et al, 2013;Holland et al, 2008;Howat et al, 2007Howat et al, , 2008Howat et al, , 2011Moon and Joughin, 2008;Rignot and Kanagaratnam, 2006;Straneo et al, 2010;Walsh et al, 2012;Zwalley et al, 2002). The forcing mechanism for the enhanced ice velocity is unclear although there is strong support for the importance of the influence of changing ocean temperatures driving glacier dynamics (e.g.…”
Section: Introductionmentioning
confidence: 99%
“…This makes it unlikely that the reconstructed temperature range between 5°C and 12°C represents SSTs within the fjord. Previous studies from Sermilik Fjord located 350 km north of Skjoldungen (Figure a) have already shown that alkenones deposited in the fjord originate mostly from inner shelf waters advected into the fjord and thus reflect values and variability of coastal waters outside the Sermilik Fjord (Andresen et al, ).…”
Section: Discussionmentioning
confidence: 88%
“…Alkenone‐based temperature reconstructions in the Nordic seas are sparse and often challenged by temperatures below a correlation limit of −5°C (Bendle et al, ; Conte et al, ; Filippova et al, ; Sicre et al, ). Previous studies have shown that the local signal in SE‐Greenland fjords can be biased by nearby highly alkenone productive waters such as south of Iceland or local upwelling, calling for cautious interpretation of the alkSST reconstruction (Andresen et al, , ). The bias that can be introduced by surface current advection in regions with a weak local production has also been demonstrated (Conte et al, ; Rühlemann & Butzin, ).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation